EVALUATING PROGNOSTIC SCORING SYSTEMS FOR ACUTE‑ON‑CHRONIC LIVER FAILURE: A 30‑DAY MORTALITY ANALYSIS - SHALAKA SHINE,; SMITHA KRISHNAMOORTHY,; AKHILESH SHINE,; SUJITH SURESH, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The aim of this study is to assess and compare the ability of chronic liver failure consortium (CLIF C) ACLF, CLIF C OF, model for end stage liver disease (MELD Na), PALBI, and Child Pugh scoring systems to predict 30 day mortality in patients diagnosed with ACLF, considering varied causes, clinical environments, and geographic regions. Methods: This ambispective observational study was conducted in a tertiary level Intensive Liver Care Unit and included adult patients with CLD who met the European Association for the study of the liver CLIF criteria for ACLF. The prognostic scores MELD Na, CLIF C ACLF, CLIF C OF, PALBI, and Child Pugh were then computed for each patient. Receiver operating characteristic (ROC) curve analysis (Delong), sensitivity, specificity, and correlation with neutrophil‐to‐lymphocyte ratio were performed using a statistical package for the social sciences v20, with p<0.05 significant. Results: In 60 ACLF patients (87% male), 60% died within 30 days. Non‑survivors were older and more often ventilated (p<0.001). Admission hypotension, hyponatremia, elevated bilirubin, international normalized ratio, creatinine, white blood cell, C-reactive protein, and lower PaO₂/FiO₂ predicted mortality (all p<0.05). ROC analysis showed all scores had an area under the curve >0.80; MELD‑Na had the highest specificity (87.5%) and positive predictive value (88.9%), whereas Child‑Pugh and PALBI offered the greatest sensitivity (75%). No score outperformed others (p>0.75). Conclusion: Although no single score outperformed others, combining MELD‑Na, Child‑Pugh, and PALBI may enhance early ACLF risk stratification, guiding resource allocation informing future dynamic, integrated prognostic models, and improving outcomes.